Docosahexaenoic acid promotes photoreceptor differentiation without altering Crx expression - Garelli, Andres (2006)
PURPOSE: The precise molecular cues required for photoreceptor development are still unknown. Pax6 and Crx are essential during early retinal development and for photoreceptor differentiation, respectively. The lipid molecule docosahexaenoic acid (DHA) has also been shown to promote photoreceptor differentiation. Pax6 expression during the early steps in photoreceptor development and whether the mutual contribution of Crx and DHA enhances photoreceptor differentiation were investigated. METHODS: Neuroblast proliferation, Crx, and Pax6 expression were investigated in rat retinas in vivo and in neuronal cultures with or without DHA. BrdU incorporation, nestin and opsin expression, apical differentiation, and axonal outgrowth were determined by phase microscopy and immunochemistry. RESULTS: Pax6 expression occurred in all proliferating retinal neuroblasts in vivo; however, after their last mitotic division, photoreceptors stopped expressing Pax6 and started expressing Crx. In vitro, photoreceptor progenitors also showed a switch from Pax6 to Crx expression immediately after they exited the cell cycle and started differentiation. In contrast, those progenitors differentiating into amacrine neurons continued expressing Pax6 and did not express Crx. Most postmitotic photoreceptors expressing Crx showed little axon development and few of them expressed opsin. The addition of DHA dramatically increased differentiation in Crx-positive photoreceptors, enhancing opsin expression, apical differentiation, and axonal outgrowth, without affecting Crx expression. CONCLUSIONS: The results suggest that Pax6 and Crx expression are mutually exclusive during photoreceptor differentiation. Onset of Crx expression may provide a permissive stage that is essential to initiate photoreceptor differentiation, but additional support of DHA, among other environmental signals, is necessary to accomplish further differentiation.